Multi-channel spiral twist extrusion (MCSTE): A novel severe plastic deformation design: Mechanical properties, structure evolution, and numerical analysis - Fouad, Dina (AUC Knowledge Fountain, 2019)
Recently, several severe plastic deformation (SPD) techniques were developed with the aim of incorporating grain refinement and strengthening metal forming technology in the industry. The interest in SPD techniques stems from their intrinsic feature of imposing large magnitudes of strain to different metals and alloys without undergoing any dimensional changes. Among the most established processes are equal channel angular pressing (ECAP), high pressure torsion (HPT), and twist Extrusion (TE). The current research work aimed for the evaluation and validation of a novel flexible and cost-effective SPD die based on TE deformation mechanics, which would entice the uptake of such promising technology in the market. Multi-Channel Spiral Twist Extrusion (MCSTE) innovative design was based on the use of customized stacked disks to host a non-circular cross-sectional billet to be processed through a TE die with a reduced twist angle (Î²) of 30o and 40o compared to 60o typically used in conventional TE dies. The introduced modifications to the conventional TE die provides a rather simple and effective solution that will translate into processing cost savings and higher die durability. In the current study, evaluation of the process was limited to investigating the influence of the number of passes, route type (A, C), twisting angle (ï¢ 30, 40o) and material (AA1100 and AA5083). Initially, a Screening Experiment was designed using Design Expert Software to validate the process and evaluate the influence of the different processing parameters. Moreover, evaluation of the effective stresses and strains associated with MCSTE processing was conducted through numerical analysis employing Simufact forming software. Mechanical properties (microhardness and tensile behavior), fracture behavior, and structural evolution using optical and scanning electron microscopy and EDS, which were employed to further explain the process deformation characteristics. Based on DoE results, Route A and punch speed of 10mm/min were set in further experimental studies. Also, it was concluded that increasing the number of passes had the most pronounced impact on the mechanical properties. Moreover, all the results suggested that the grain refinement strongly depended on the die geometry and strain hardening behavior of the material. In all cases, the hardness and tensile properties increased monotonically as a function of increasing the number of passes with insignificant reduction in ductility for both tested twist angles. The highest improvements and grain refinement were attained after deformation via angle ï¢ 40o for both materials. The finest average grain size attained in AA1100 post 4-passes was 28.5 microns and 1.5 microns in AA5083 post 1-pass of MCSTE. The comparison between the FEM finding and empirical findings revealed that the increase in properties is mainly associated with the increase in average strain induced (~0.9) which approached that induced by typical TE dies (ï¢ = 60o) of 1.2. Additionally, the processing loads and effective stresses induced by MCSTE were much lower compared to conventional TE processing, which suggests prospects of prolonging the lifetime of the die and enhancing its durability. Moreover, inspection of the distribution of properties along the longitudinal and transverse cross-section of the MCSTE (ï¢ = 30o) extrudates and optical micrographs of the microstructure indicated a rather homogenous distribution compared to that achieved in MCSTE (ï¢ = 40o) extrudates. Furthermore, analysis of tensile fracture surfaces using scanning electron microscopy (SEM) showed a ductile mode of failure that initiated at segregated impurities and Al-Mg precipitates in AA1100 and AA5083, respectively. The detailed analysis presented herein; validates the effectiveness of MCSTE as an SPD tool for grain refinement with a favorable potential for industrial applications.